2022
DOI: 10.3389/fonc.2022.951485
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported gastrointestinal symptoms following surgery for gastric cancer and the relative risk factors

Abstract: PurposeThe study aims to assess the incidence of short-term patient-reported postoperative gastrointestinal symptoms (PGISs) after gastric cancer surgery and explore the relative risk factors for the symptoms.MethodsPatients with radical gastrectomy were included for this retrospective and observational study. Symptoms extracted from the MD Anderson Symptom Inventory Gastrointestinal Cancer Module (MDASI-GI) were collected in postdischarge week (PDW) 1 and postoperative month (POM) 1. The distributing states o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A prospective single institution cohort study of 356 patients in China used MDASI-GI to assess patient-reported gastrointestinal symptoms after gastrectomy. 7 Gastrointestinal symptoms were reported by 71% of patients 1 week after discharge. The most frequent symptom was F I G U R 1 Percentage of patients who underwent gastrectomy for cancers at a single cancer institution and reported symptoms as moderate to severe in the preoperative period and during postoperative days 1-3 or during postoperative days 4-7.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A prospective single institution cohort study of 356 patients in China used MDASI-GI to assess patient-reported gastrointestinal symptoms after gastrectomy. 7 Gastrointestinal symptoms were reported by 71% of patients 1 week after discharge. The most frequent symptom was F I G U R 1 Percentage of patients who underwent gastrectomy for cancers at a single cancer institution and reported symptoms as moderate to severe in the preoperative period and during postoperative days 1-3 or during postoperative days 4-7.…”
Section: Discussionmentioning
confidence: 98%
“…The results of this study are concordant with prior work describing high symptom burden after gastric surgery. A prospective single institution cohort study of 356 patients in China used MDASI‐GI to assess patient‐reported gastrointestinal symptoms after gastrectomy 7 . Gastrointestinal symptoms were reported by 71% of patients 1 week after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…This scale is speci cally designed to measure the occurrence and burden of symptoms in the gastrointestinal cancer population. It is a module of the larger Gastrointestinal Cancer Assessment Scale, developed based on general assessment scales [23][24][25]. The translated version of this scale has been widely used in China for measuring and assessing patient symptoms [26,27].…”
Section: The MD Anderson Symptom Inventory Gastrointestinal Version(m...mentioning
confidence: 99%
“…2,3 Up to 90% of patients who have undergone gastrectomy report experiencing gastrointestinal symptoms, including dysphagia, abdominal distension, pain, diarrhea, and, vomiting leading to malnutrition, which is associated with a poor prognosis. [4][5][6] One of the causes of maldigestion is exocrine pancreatic insufficiency (EPI), a disorder characterized by insufficient or abnormal production or activity of pancreatic juice. EPI can lead to steatorrhea, stomach distension, flatulence, and weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Survival rates for gastric cancer are improving, particularly since the introduction of neoadjuvant therapy; however, surgery remains the mainstay of curative treatment; total gastrectomy is the acknowledged surgical treatment for gastric cancer 2,3 . Up to 90% of patients who have undergone gastrectomy report experiencing gastrointestinal symptoms, including dysphagia, abdominal distension, pain, diarrhea, and, vomiting leading to malnutrition, which is associated with a poor prognosis 4–6 …”
Section: Introductionmentioning
confidence: 99%